Sifat Dasar Tanaman Mengkuang (Pandanus artocarpus Griff) Basic Properties of Mengkuang Plant (Pandanus artocarpus Griff) - Hikma Yanti; Wasrin Syafii; Nyoman J Wistara; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2018)
The aim of this research were to determine the extractive, α-cellulose, hemicellulose, lignin, and sugar composition of hemicelluose for raw materials and pulp of mengkuang (Pandanus artocarpus Griff) leave and stem. Delignification was carried out by alkaline process with NaOH 20% and 25% at 170 oC for 4 h. The chemical and physical analyses were done using Fourier Transform Infrared Spectroscopy, X-Ray Diffraction, High Performance Liquid Chromatography, and Scanning Electron Microscopy. The leaves and stem of mengkuang containing extracts of 6.99% and 4.80%, cellulose 35.02% and 40.29%, hemicellulose 33.12% and 31.19%, lignin 29.10% and 26.84%, respectively. The syringyl, guaiacyl, and p-hydroxyphenil composition in mengkuang leaves and steam were 40.00%, 41.82%, 19.24% and 39.81%, 41.82%, 18.37%. The hemicellulose in the leaves and stem consisted of glucose, arabinose, xylose, mannose, rhamnose, and galactose. The highest pulp yield (41.71%) was obtained from pretreatment of 20% NaOH in the stem. Pulp of leaves and stem contained α cellulose, hemicellulose, and total lignin content of 88.19%, 7.95%, 14.36%, and 88.27%, 10.17%, 13.83%. The highest crystallinity of pulp (70.00%) was obtained from the stem at a concentration of 25% NaOH, and the lowest (58.18%) was obtained from the leaves at a concentration of 25% NaOH.